2020
DOI: 10.1186/s10195-020-00549-5
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of risk factors for deep infection in lower limb Gustilo–Anderson type III fractures

Abstract: Background: Open fractures are among the most severe injuries observed in orthopedic patients. Treating open fractures is difficult because such patients with infections may require multiple operations and amputations. Furthermore, only a few studies have focused on antibiotic prophylaxis in open fractures and evaluated how to cover lost soft tissue to increase the success rate of reconstruction. We evaluated the risk factors for deep infection in lower limb Gustilo-Anderson (G-A) type III fractures. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…These results may be related to the small size of our population. Other risk factors have been previously identified: male gender, smoking, polytrauma, Gustilo grade III classification, and contaminated wounds [ 4 , 7 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be related to the small size of our population. Other risk factors have been previously identified: male gender, smoking, polytrauma, Gustilo grade III classification, and contaminated wounds [ 4 , 7 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of infection, Gustilo classification, smoking, diabetes, time to antibiotic therapy initiation, and shorter duration of antibiotic prophylaxis have been identified as risk factors for the occurrence of postoperative infections [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the severity of open lower leg fractures, we evaluated the Gustilo-Anderson Classi cation of each patient. [11,12]. In the case of bone loss, which is a major condition for amputation, bone loss of 5 cm or more was con rmed by radiological evaluation.…”
Section: Assessmentmentioning
confidence: 99%
“…1,2 In cases of open tibial fractures, recent studies have found that the combination of vancomycin and meropenem as first-line antibiotic therapy covers up to 93% to 96% of the encountered bacteria causing infection, most frequently being Staphylococcus aureus, Enterococcus spp., Pseudomonas aeruginosa, Enterobacter species, and coagulase-negative staphylococci (CoNS). 1,2,10 Supported by the current European Bone and Joint Infection Society (EBJIS) guidelines on prevention of fracture-related infections, 11 the diverse contamination profile demands a broad antibiotic prophylactic spectrum encompassing both Gram-positive and Gramnegative bacteria. 12 When administering antibiotics to prevent infection of a contaminated open fracture, it is essential that antibiotic target site concentrations, as a minimum, reach and remain above relevant bacteria's minimal inhibitory concentrations (MICs) for a sufficient amount of time.…”
Section: Introductionmentioning
confidence: 99%